Broadband continuous absorber based on dual-mode coupling resonance - Liu, Haixia; Liu, Yu; Li, Wenjie; Li, Tianqi; Zhang, Shashi (Frontiers in Physics, 2024)
The continuous detection of visible to near-infrared light is a critical focus in optics due to its broad application value. To address this challenge, we present a graphene-based gradient groove metasurface (GGM) that enables efficient broadband absorption by simultaneously exciting surface plasmon polariton (SPP) resonance and Fabry-Pérot (FP)-like cavity resonance within multiple grooves. This dual-mode coupling effectively mitigates SPP losses and overcomes the size constraints of FP cavities, allowing for broadband, angle-insensitive absorption from 600 to 1,100 nm with an average absorption rate of 87.5%. Finite element simulations further show that variations in groove fillet radius variations from 5 nm to 20 nm and sidewall inclination variations from 0.02 to 0.22, result in absorption deviations of less than 2% and 6%, respectively, demonstrating the structure’s robustness against industrial processing errors. These findings suggest that the proposed GGM structure can significantly expand the application range of photodetectors in the visible to near-infrared wavelength bands, offering a promising solution for optical sensing applications.